2020
DOI: 10.12913/22998624/124553
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Service Life of Metal-Polymer Gears Made of Glass and Carbon Fibre-Reinforced Polyamide, Considering the Impact of Height Correction

Abstract: Calculation methods for predicting the service life of metal-polymer gears with height correction are proposed. Two methods for gear service life estimation are presented: a simplified method that assumes constant tooth interaction conditions and an improved method that takes into account wear-induced changes in tooth interaction conditions. Spur cylindrical gears with a steel gear and a pinion made of polyamide composite reinforced with carbon and glass fibres are studied. The effect of height correction on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…According to Chernets, 19 Chernets and Kornienko 20 Chernets et al, 21 Chernets et al, 22 and Chernets and Chernets 23 the teeth linear wear h ′ kj of the MP gears (Figure 1) at selected points j of their contact during one interaction is determined by the formula: where j = 1, 2, 3, …, s , t = 2 b j / v 0 , v 0 = ω 1 r 1 sinα, τ S = 0.5 R m for polymer composites, and τ S = 0.35 R m for steel.…”
Section: Methods For Solving the Wear Contact Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Chernets, 19 Chernets and Kornienko 20 Chernets et al, 21 Chernets et al, 22 and Chernets and Chernets 23 the teeth linear wear h ′ kj of the MP gears (Figure 1) at selected points j of their contact during one interaction is determined by the formula: where j = 1, 2, 3, …, s , t = 2 b j / v 0 , v 0 = ω 1 r 1 sinα, τ S = 0.5 R m for polymer composites, and τ S = 0.35 R m for steel.…”
Section: Methods For Solving the Wear Contact Problemmentioning
confidence: 99%
“…Two methods were used to calculate the service life of gears: 2025 simplified – Under constant conditions of teeth tribocontact interaction in the engagement when p j max = const , h ′ kj = const and the total teeth wear h max = n k h ′ kj ; improved (cumulative – accumulative) – Under variable conditions of teeth tribocontact interaction in the engagement, that is, at p jh max = var and h ′ kjn = var after each revolution (discrete interaction) or after a certain number of revolutions (block interaction). According to the simplified method, 22,23 the minimum durability t min before achieving the acceptable wear h k* at a certain point of contact is calculated as follows: When applying the improved method with variable conditions of tribocontact interaction, the procedure for calculating the durability is more complicated. 22,23 Wear of the teeth causes an increase in the initial radii of profile curvature, which leads to a decrease in the maximum contact pressures p j max and increases the width of the contact area 2 b j .…”
Section: Methods For Solving the Wear Contact Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…For instances, Mao et al 8 proposed an approach for acetal gear transition torque prediction, which was based on the link between polymer gear wear rate and its surface temperature. Myron et al 18 proposed calculation methods for predicting the service life of metal‐polymer gears with height correction, and they found that with the improved method, the service life of the gear was by up to 1.3 times longer. However, with the emergence and development of artificial intelligence technology, the life prediction accuracy of the traditional method is too low, which can no longer meet the anti‐fatigue design of the new generation of polymer gears.…”
Section: Introductionmentioning
confidence: 99%